Pengaruh Terapi Relaksasi Autogenic terhadap Denyut Nadi Ibu Anak Tuna Grahita - Nani, Desiyani (Jurnal Keperawatan Soedirman, 2014)
Autogenic relaxation technique gives a soothing effect on the mind and body, and is used to overcome physical disorders associated with excessive emotional response in the mother especially in mothers whose have children with mental retardation whose often have symptoms of somatization without or with physical impairments.This study aims to identify the effect of autogenic relaxation therapy on the pulse rate on mothers of children with mental retardation. The study design used was a non randomized experiment Quasy pretest- posttest with control group design. Total sample of 29 respondents who were counted pulse rate before and after autogenic relaxation therapy for 3 days. The test data is done by paired t - test statistk test and independent t - test.The results showed no significant difference between pulse rate between the intervention group and the control group with p:0.717 ( p more than 0.05 ) .There is no significant difference in pulse rate between the intervention group and the control group.